Społeczna odpowiedzialność konsumenta - Michalski, Michał (Annales. Etyka w Życiu Gospodarczym, 2008)
In our contemporary literature and academic discourse we often see how popular the topic of corporate social responsibility is. In my opinion another problem – tightly linked to this – and strongly influencing our business life is consumer’s activity. This second part of business relations is often associated rather with legal demands and customer’s protection. The purpose of my article is to show how consumer social responsibility can help not only corporations, but all those involved in the market exchange to contribute to the common good and improve quality of millions of transactions people make every day. To become real, this responsibility needs effort – courage to witness by expressing consumer’s opinion and education. The first aspect shows how important action is in revealing values and introducing ethics into everyday market activity, the second shows that emphasizing basic economical education and expecting thorough information from companies can help build and enhance consumer awareness. In my paper I am also trying to show the contribution of Catholic Social Thought to the problem of social responsibility.